Optimalization of preparation of apo-cytochrome b(5) utilizing apo-myoglobin - Mrázová, Barbora; Martínková, Markéta; Martínek, Václav; Frei, Eva; Stiborová, Marie (Interdisciplinary toxicology, 2008)
Cytochrome b(5) (cyt b(5)), a component of endoplasmic reticulum membrane, plays a role in modulation of enzymatic activity of some cytochrome P450 (CYP) enzymes. The effect of apo-cytochrome b(5) on this enzymatic system has not been investigated in details, because preparation of cyt b(5) as a pure protein failed in many laboratories. In order to prepare the native apo-cytochrome b(5) in a large scale we utilized a protein with higher affinity toward the heme; the apo-myoglobin from the equine skeletal muscle. In the first step, we extracted heme moiety from the native myoglobin by butanone extraction. Than the effect of pH on spontaneous heme release from both proteins was investigated: purified rabbit cyt b(5) as well as equine skeletal muscle myoglobin. The prepared apo-myoglobin was incubated with the cyt b(5) and heme transfer was monitored as a shift of absorption maximum from 413 to 409 nm in pH varying between 3-6 (10 mM KH(2)PO(4), pH 3-6). Here, we obtained 43 mg of the equine skeletal muscle apo-myoglobin (43% yield). The optimal pH range for heme transfer from cyt b(5) into apo-myoglobin was between 4.2 and 5. Native apo-cytochrome b(5) was successfully prepared using procedure described here.
Keywords: pH; butanon extraction; cytochrome b5; apo-myoglobin